Potensi Injeksi Intra-artikular Sel Punca Mesenkimal sebagai Terapi Osteoartritis Lutut:: Tinjauan Sistematis Mengenai Efektivitas dan Profil Keamanan - Vincentius Mario Yusuf; Ivena Leonita; Aurielle Annalicia Setiawan; Muhammad Yusuf (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Osteoarthritis (OA) is a chronic multifactorial disease (inflammatory, mechanical, and metabolic) that is most often found in knee joints. Current OA therapy mostly uses NSAIDs as symptomatic treatment, with severe side-effects in long-term use. Therefore, a new causative therapy is needed that can minimize side effects and also has high efficacy. Mesenchymal stem cells (MSC) have promising potential for further research as a novel therapy for OA. Methods: This systematic review was conducted by including validated studies extracted from PubMed, Cochrane, ScienceDirect, dan ProQuest databases, using the keywords “knee osteoarthritis” and “mesenchymal stem cells” with a publication range of 2011-2021. RCT studies examining the use of intra-articular injection of MSC for knee OA were included. Outcome measures used were Visual Analog Scale (VAS), Western Ontario and McMaster University Osteoarthritis Index (WOMAC), MRI results (WORMS, cartilage volume, cartilage defect size), and side effects. Discussion: MSC can improve clinical assessment of OA, as seen from the significantly improved WOMAC and VAS scores and also radiological improvement, as seen from the improved WORMS scores, cartilage defects and volume. MSCs have anti-inflammatory and immunomodulatory potential, and are able to stimulate cartilage-like cells, which can assist in the recovery and prevention of further development of OA. Adverse effects are generally mild and self-limiting, therefore safe for human use. Conclusion: Intra-articular injection of MSC is potentially effective as a method of knee OA therapy with minimal side effects.